Survey On Father’s : Knowledge About Breastfeeding - Yunita, Prasida (Journal of health research and technology, 2024)
Exclusive breastfeeding means the baby receives only breast milk and no other liquids, solids, or even water, except oral rehydration solutions or drops/syrups of vitamins, minerals, or medicines. The success of exclusive breastfeeding for 6 months cannot be separated from the support and role of family, such as parents, in-laws, and especially the support of the husband as the closest person. Good knowledge is needed to succeed in breastfeeding, but fathers' knowledge of the importance of breastfeeding is still shallow, many fathers / prospective fathers do not understand the importance of breastfeeding and its benefits for babies and mothers. Father/partner is one of the most significant factors for breastfeeding success. Fathers/partners influence the decision to breastfeed children and their support influences the experience and duration of breastfeeding. The purpose of this study was to find out how fathers know about breastfeeding. The type of research used is qualitative. The population in this study was prospective fathers of III trimester pregnant women (32-40 weeks) as many as 84 people with non-probability sampling techniques with purposive sampling methods. The instrument used is a questionnaire in the form of a checklist sheet that has been tested for validity. The results obtained by most respondents or 51 (60.7%) respondents are less knowledgeable about breastfeeding, both about the benefits of exclusive breastfeeding for the growth and development of babies, how to provide breast milk, food to increase milk production, and complicating the breastfeeding process. Lack of knowledge of husbands challenging breastfeeding because adequate emphasis has not been given to the promotion of breastfeeding. They need a platform managed by health professionals who can help them and allow them to absorb information and apply it and feel confident and competent as an engaged parent.